MODERN INNOVATIVE METHODS OF TEACHING STUDENTS TO COMPETENT USE VISUALIZATION MEANS (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2023)
The article analyzes the block of psychological and pedagogical disciplines, with the purpose ofrevealing and substantiated gaps in the teaching of students of pedagogical universities to competent, effective use ofvisual means of teaching, which use the visual acuity in the educational process of the school.Specifies the disadvantages of this block of disciplines in preparing students, future technology teachers, forprofessional activities. The authors proposed ways to overcome the psychological and pedagogical barriers formed bysome school leaders and individual educators to effectively implement visual teaching aids.The authors concretize the proposals, taking into account the shortcomings revealed by him, to improve the training of future technology teachers. This is a mandatory formulation of pedagogical skills of using visual means ineducational work when students study the disciplines of the psycho-pedagogical cycle and the formation of students ofpedagogical skills for the study of modern visual and technical means of study.The study and allotted pedagogical conditions, which ensure the effective functioning of the system of trainingstudents, future technology teachers to the competence of its use of means of visibility.